Factor Analysis of Factors Affecting Addiction and its Prevention in Secondary School Male Students in Hamadan - Kazemi, Seyyed Sajjad; Mazaheri, Amir Hossein (International Journal of Psychosocial Rehabilitation, 2020)
Background and Purpose; the main purpose of this study was to analyze the effective factors on addiction and its prevention in high school male students in Hamadan. Factor analysis was a multivariate correlational research method.Methodology; the statistical population of this study consisted of all male secondary school adolescents in Hamadan who were 15-19 years old. 373 students were selected by simple random sampling based on Cochran formula. Measurement tools include a researcher-made questionnaire by Bagheri et al. (2005).This questionnaire consists of two parts: demographic characteristics, tendency factors and methods of drug use prevention.Results; the validity of the questionnaire was confirmed based on the collective opinion of the experts, Cronbach's alpha coefficient (0.89) was used to determine the reliability, this indicates the appropriateness of the research instrument. The collected data were analyzed using SPSS software. The results of factor analysis indicate that: Of the 28 questions asked, 6 factors were extracted, these six factors include: family, educational, supervisory-executive, social, economic, security.